Carcinogenic organic residual compounds readsorbed on thermally reduced graphene materials are released at low temperature - Ambrosi, Adriano (2014)
The preliminary oxidation of graphite to graphite oxide followed by a thermal exfoliation is one of the methods most frequently employed in the preparation of graphene. Such thermally reduced graphene can be widely used for several applications that range from coatings to sensing device fabrication. It is therefore important to investigate in detail the fabrication procedure, the structural features of the resulting graphene, and its potential toxicological effects. Low-molecular-weight and carcinogenic compounds are known to be generated during the thermal reduction/exfoliation of graphite oxide. Such compounds are readsorbed onto the reduced material during the cooling process. We investigate here the composition of the organic compounds that are adsorbed onto the graphene material and show that they can be easily released during the following processing steps even at temperatures as low as 50 °C. Some of the released organic compounds are classified as highly carcinogenic. The results shown here are important not only from a chemical point of view to better understand the composition and properties of the graphene material produced, but also to bring attention to the potential toxicological effects that the synthesis itself or the post-production processes can cause.